Contextualizing Islamic Ecology: Representation of Environmental Crisis in Post-9/11 Pakistani Fiction - Muhammad Shoaib; Dr. Sobia Mubarak (jihat-ul-islam, 2020)
The US-led War on Afghanistan in the wake of 9/11 has led to far-reaching repercussions for the climate of the region, affecting weather patterns, bird migration routes, human and animal health, water resources and food production. Literary and non-literary discourses have responded significantly to this crisis. But there is need to contextualize Islamic injunctions and principles on the protection of physical and living environment. This article addresses this gap by using Islamic ecology lenses to analyse the representation of environmental crises in a selection of post-9/11 Pakistani novels in English. Attending to the fictional representations of environmental deterioration in Feryal Ali Gauhar’s No Space for Further Burials (2007) and Nadeem Aslam’s The Wasted Vigil (2008), the article highlights the need to integrate Islamic discourse on ecology in the current environmental epistemology to counter the escalating environmental crises. The research problematizes the nexus of militarism and neo-colonial capitalistic agenda that, in collusion with the existing social dualisms, aims at wresting the natural resources of the third world countries, pushing them into environmental precarity. It is argued that an ethic based on greater ecological inclusion can be generated from the environmental parameters provided by Islam, the major religion in the area under discussion.